SELEKSI CALON PEGAWAI NEGERI SIPIL (CPNS) MENURUT PERATURAN MENTERI PENDAYAGUNAAN APARATUR NEGARA DAN REFORMASI BIROKRASI REPUBLIK INDONESIA NOMOR 22 TAHUN 2017 TENTANG NILAI AMBANG BATAS TES KOMPETENSI DASAR CPNS TAHUN 2017 - S, Erick Junata (Jurnal Cahaya Keadilan, 2017)
Publics Servant Prospective acceptance Civil or succeeding one to be abbreviated CPNS constitutes one of momentum the most hankered by society. A lot of it gives a damn society that follows to sort CPNS that arranged by ministry Region Office Sentences And Riaus archipelago Human Right where phase early participant has to perform PAINT test, Physical checking, and Interview for applicant s 1 and d. 3. SMAS ladder participant little bit different, after sits for an examination PAINT, they are mandatory follow to essay kesampataan, and Physical Watch Test and skill and Interview. Base background upon, therefore writer lift research aim as follows: first, In as much as which transparency sorts Civil Public Servant Candidate at Environmentally ministries Territorial Office Sentence and Riaus archipelago Human Right. Both of, Any kind constraint which is faced deep Prospective accepting performing Civil Public Servant at Environmentally ministries Territorial Office Sentence and Riaus archipelago Human Right.Methode research used in here is empiric with used technic for taked document is interview.